Iot: A Boon for Farming - Yadav, Mohit; Singh, Priya; Sharma, Anurag (International Journal of Computer Sciences and Engineering, 2025)
Agriculture plays a very important role in the development of any country. As in India, about 70% of the population depends upon the farming and 1/3rd of the capital comes from agriculture. Now the agriculture area in India is diminishing day by day, which is affecting the production capacity of the ecosystem, development of the country, capital of the country and mainly farmers of India. The main purposes of this article to overcome these problems which come directly, indirectly in farming by using the recent technology called IoT (Internet of Things) and provide a perfect solution. IoT has shared a network of an object embedded with electronics, software, sensor and many more with the internet for collecting and exchanging the data. One of the important application of IoT is Smart Farming. In Smart Farming, we discuss the implementation of IoT in Irrigation System, Large Farming Operation, Organic Farming, Family Farming, Production System, Monitoring System to analyze the Weather, Crop, Soil condition.